Penentuan Prioritas Pembangunan Melalui Analisis Sektor-Sektor Potensial di Kabupaten Gianyar - Riantika, Ida Bagus Adytia; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 7, Juli 2017 (pp. 1157 - 1394), 2017)
The potential of the area in order to regional development needs to recognize the potential to be effective and efficient regional planning. The purpose of supporting a research done is to analyze the sector that has the potential to be developed in Gianyar and Knowing and analyze whether potential sector development priorities right in Gianyar. This research was conducted in Gianyar which data were taken in the Central Bureau of Statistics. In this study use four tools of analysis, engineering analysis Location Quotient (LQ), Analysis of Dynamic Location Quotient (DLQ), the growth rate model analysis, overlay analysis and in qualitative analysis. From this research in priority sectors get that result of major developed in Gianyar is a provider of accommodation and eating and drinking, the real estate sector, and health services. Economic sectors in Gianyar that are developed, managed and [1] handled more leverage so as to produce a sector that could be a priority as well as the maximum added value later. *) E-mail: goes.rian88@gmail.com
Keywords: Prioritas, Potensial, Pembangunan, Pertumbuhan, PDRB